1980
DOI: 10.1128/aac.17.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of peptidoglycan in Pseudomonas aeruginosa: comparison of the inhibitory effects of cefotaxime, its anti isomer, and the syn S-oxide compound

Abstract: The intrinsic effect of three novel methoxyimino derivatives of cephalosporin (cefotaxime [syn HR 756]; its anti isomer, R 02 5328 A; and the syn S-oxide derivative, HR 109) on the biosynthesis of peptidoglycan ofPseudomonas aeruginosa X-48 was investigated. Cefotaxime at very low concentrations (50% inhibition at 0.025 ,ug/ml) inhibited the transpeptidase reaction which catalyzes the incorporation and attachment of newly synthesized peptidoglycan to the preexisting cell wall sacculus. The S-oxide compound, HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The first observation is in good agreement with that reported by Labia et al (1980). The second, however, does not apply to the DD-carboxypeptidase and transpeptidase activities of ether-treated Pseudomonas aeruginosa cells, for which Mirelman & Nuchamowitz (1980) reported a much decreased effect on the anti isomer.…”
Section: Discussionsupporting
confidence: 88%
“…The first observation is in good agreement with that reported by Labia et al (1980). The second, however, does not apply to the DD-carboxypeptidase and transpeptidase activities of ether-treated Pseudomonas aeruginosa cells, for which Mirelman & Nuchamowitz (1980) reported a much decreased effect on the anti isomer.…”
Section: Discussionsupporting
confidence: 88%
“…21,22) Some studies have demonstrated that impermeability of the bacterial plasma membrane plays an important role in resistance to kanamycin. 23) Therefore, if the entry of kanamycin into the cytoplasm is increased by changes in the permeability of the plasma membrane, the antibacterial activity of kanamycin, against kanamycin-resistant bacterial strains, could be increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical strain, the only antibiotics tested that affected this reaction were cefotaxime and its analog LY 97962. The reason for this remarkable and apparently exclusive mode of action of cefotaxime is extremely intriguing, and it certainly warrants an in-depth investigation and comparison at the molecular level of the mode of interaction between different 8-lactams and the transpeptidase systems of the resistant and sensitive strains (14).…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic reactions which catalyze the attachment of newly synthesized peptidoglycan to the preexisting cell wall material (transpeptidases) are very sensitive to most ,B-lactam antibiotics (13,14,16).…”
mentioning
confidence: 99%